Readability thresholds : xenography and speculative fiction - Bekavac, Luka, književnik (Array, 2020)
The unreadable and the illegible tend to be treated as the “other” of writing. Playing on one of the meanings of xenography – writing in a language unknown to the writer – this paper explores the possibility that the metaphorical “gravity assist” of literature, rather than engaging the resources of content and imagination, actually resides in the cognitively inaccessible layers of writing as a material phenomenon. If we accept Harman’s definition of realism as something that can’t be translated into human knowledge without energy loss, regions of unintelligibility in literary writing take on a completely different meaning, and appear as zones coinciding with the asemic material exteriority, equally unavailable to thought and mimesis. Writings of Thomas Ligotti (The Red Tower), Reza Negarestani (Cyclonopedia) and Mark Z. Danielewski (The Familiar) are examined in the light of various atypical formal devices they use to convey a certain “otherness,” introducing varying degrees of unreadability as a response to the “inscrutability of the Real itself” (Fisher) and enforcing new types of non-hierarchical distribution of agency between writer, reader and text.